18F-Fluorodeoxyglucose Uptake in Bilateral Diaphragmatic Crura: A Relatively Uncommon Benign Variant Noted in a Treated Case of Extraosseous Paraspinal Ewing's Sarcoma - Baberwal, Parth; Sonavane, Sunita N.; Basu, Sandip (World Journal of Nuclear Medicine, 2024)
A toddler was diagnosed with extraosseous Ewing's sarcoma, primary large epidural paraspinal soft tissue in the lumbar region encasing the cord and neural foramen from D12–L1 to L4–L5. After eight cycles of induction chemotherapy with vincristine, doxorubicin, and cyclophosphamide alternating with etoposide and ifosfamide, 18F-FDG positron emission tomography/computed tomography (18F-FDG-PET/CT) scan confirmed no active disease. Later external beam radiotherapy (EBRT) at D10–L5 was completed. At 3 months follow-up, 18F-FDG-PET/CT reconfirmed no residual/active disease; however, a new incidental finding of diffuse benign bilateral diaphragmatic 18F-FDG uptake was noted in the clinically asymptomatic patient, which remained unexplained.
Keywords: extraosseous paraspinal Ewing's sarcoma; bilateral diaphragmatic crura; FDG-PET/CT; benign variant; nonspecific FDG uptake